Motor Control and Neural Plasticity through Interhemispheric Interactions - Naoyuki Takeuchi; Yutaka Oouchida; Shin-Ichi Izumi (Neural Plasticity)
The corpus callosum, which is the largest white matter structure in the human brain, connects the 2 cerebral hemispheres. It plays a crucial role in maintaining the independent processing of the hemispheres and in integrating information between both hemispheres. The functional integrity of interhemispheric interactions can be tested electrophysiologically in humans by using transcranial magnetic stimulation, electroencephalography, and functional magnetic resonance imaging. As a brain structural imaging, diffusion tensor imaging has revealed the microstructural connectivity underlying interhemispheric interactions. Sex, age, and motor training in addition to the size of the corpus callosum influence interhemispheric interactions. Several neurological disorders change hemispheric asymmetry directly by impairing the corpus callosum. Moreover, stroke lesions and unilateral peripheral impairments such as amputation alter interhemispheric interactions indirectly. Noninvasive brain stimulation changes the interhemispheric interactions between both motor cortices. Recently, these brain stimulation techniques were applied in the clinical rehabilitation of patients with stroke by ameliorating the deteriorated modulation of interhemispheric interactions. Here, we review the interhemispheric interactions and mechanisms underlying the pathogenesis of these interactions and propose rehabilitative approaches for appropriate cortical reorganization.